3D face and body reconstruction via volumetric regression networks - Jackson, Aaron S. (2019)
3D Face reconstruction is the process of estimating the full 3D geometry of a human's face from one or more images. Applications of 3D face reconstruction span many areas, from personalisation of video games and trying on accessories online, to measuring emotional arousal for psychological studies and in medicine, such as simulating the result of reconstructive surgery. Approaches to 3D face reconstruction generally depend on a 3D Morphable Model (3DMM) - a parametric model, where the shape, pose and expression can be adjusted using a small number of parameters. While methods based on such techniques can work well on frontal images, they often begin to fail on cases of large pose, difficult expression, occlusion, and bad lighting. Additionally, encoding detail in so few parameters is not possible.